The Great Design: Order and Intelligence in Nature - Frances Mason; J. Arthur Thomson 1861-1933 (UK Duckworth, 1934)
edited by Frances Mason; introduction by Sir J. Arthur Thomson
Introduction. by Sir J. A. Thomson.--Behold the stars! By R. G. Aitken.--Radiation, by J. A. Crowther.--The universe as a whole, by A. S. Eve.--The earth as the home of man, by Bailey Willis.--The ascent of mind, by C. L. Morgan.--The oneness and uniqueness of life, by E. W. MacBride.--Adaptations in the plant world, by C. S. Gager.--The chemical romance of the green leaf, by H. E. Armstrong.--Intelligent plan in nature, by M. M. Metcalf.--Design and purpose in the universe, by Sir Oliver Lodge.--The mystery of nature, by Sir Francis Younghusband.--Unity and intelligence in nature, by D. F. Fraser-Harris.--The breakdown of materialism, by Hans Driesch.--The wonder of life, by Sir J. A. Thomson
Aitken, Robert Grant, 1864-1951 . Crowther, James Arnold, b. 1883 . Eve, A. S. (Arthur Stewart), 1862-1948 . Willis, Bailey, 1857-1949 . Morgan, C. Lloyd (Conwy Lloyd), 1852-1936 . MacBride, E. W. (Ernest William), 1866-1940 . Gager, C. Stuart (Charles Stuart), 1872-1943 . Armstrong, Henry Edward, 1848-1937 . Metcalf, Maynard Mayo, 1868-1940 . Lodge, Oliver, Sir, 1851-1940 . Younghusband, Francis Edward, Sir, 1863-1942 . Fraser-Harris, David Fraser, 1867-1937 . Driesch, Hans, 1867-1941
Keywords: Natural Theology and Apologetics (3GddGghJ GdfXQj (B- (3GddGghJ GdOaGYjs; Theology; Cosmogony; Evolution; Religion and science